The changing trend of cardiovascular disease and its clinical characteristics in Ethiopia: hospital‑based observational study - Tefera, Yonas Getaye; Abegaz, Tadesse Melaku; Abebe, Tamrat Befekadu; Mekuria, Abebe Basazn (Vascular health and risk management, 2017)
The aim of this study was to assess the pattern of cardiovascular diseases (CVDs), their clinical characteristics, and associated factors in the outpatient department of the chronic illness clinic of Gondar University Referral Hospital. A retrospective cross-sectional study was conducted among patients on follow-up at the outpatient chronic illness clinic of the hospital from October 2010 to October 2015. The source population for the study included patients with a diagnosis of CVD whose medical records have the required socio-demographic information during the study period. The data were collected from August 2015 to December 2015. Chi-square and binary logistic regression tests were performed to test the significance of difference among predictive variables and CVDs. Of 1105 patient medical records, 862 fulfilled the inclusion criteria. The majority of the patients were females (65%) and living in urban areas (62.7%). Hypertension accounted for the majority (62.3%) of CVDs followed by heart failure (HF) (23.9%). Headache was the leading chief complaint among the patients (37.7%) upon diagnosis and was the prominent clinical feature in more than half of the patients during their course of follow-up. Higher proportions of dyslipidemia (85.7%), hypertension (72.8%), and ischemic heart disease (IHD) (73.2%) were associated with urban residency ( <0.01). Patients from rural areas (crude odds ratio [COR] =1.306 [95% confidence interval 1.026-2.166], adjusted odds ratio [AOR] =1.272 [95% confidence interval 1.017-2.030]) and those with comorbidity illnesses (COR= 1.813 [1.279-2.782], AOR =1.551 [95% confidence interval 1.177-2.705]) were more likely to have poor CVD outcome ( <0.05). Hypertension was found to be the most frequent CVD followed by HF, and hypertensive heart disease was the leading cause of cardiac diseases. Most of the patients had improved assessment in the last follow-up, but patients from rural regions and those with comorbidty had higher likelihood of poor cardiovascular outcome.